When Worse is Better: Economic Policy Making in the Two Irelands of the mid 1950s - Birnie, Esmond; Brownlow, Graham (Statistical and Social Inquiry Society of Ireland, 2023)
Economic Development (1958) remains a document associated with T.K. Whitaker’s role in Ireland’s shift away from protectionist economics. Whatever the report’s exact role in changing the direction of Irish economic strategy, the reputation of Economic Development greatly exceeds that of An Economic Survey of Northern Ireland (1957), which was a report authored by Isles and Cuthbert, two Belfast-based academics. The economic analysis contained within both reports/strategy documents along with their respective fates forms the focus of this paper. The relative failure to implement the analysis set out by Isles and Cuthbert, as well as its relative obscurity, rests on a range of factors. Perceptions of the acuteness of the respective economic problems, issues of authorship, the close interaction between political leadership and major industries/firms in Northern Ireland and the range of actionable policy prescriptions presented in a report are all important in explaining the contemporary and subsequent receptions.
(read before the Society, 27th October 2022)
Keywords: economic strategy; comparative economic history; implementation; 314.15